2014
DOI: 10.1364/oe.22.001726
|View full text |Cite
|
Sign up to set email alerts
|

Modulation response of a long-cavity, gain-levered quantum-dot semiconductor laser

Abstract: Abstract:The gain-lever effect enhances the modulation efficiency of a semiconductor laser when compared to modulating the entire laser. This technique is investigated in a long-cavity multi-section quantum-dot laser where the length of the modulation section is varied to achieve 14:2, 15:1 and 0:16 gain-to-modulation section ratios. In this work, the gain-levered modulation configuration resulted in an increase in modulation efficiency by as much as 16 dB. This investigation also found that the 3-dB modulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…A 22 dB modulation efficiency increase was also realized using a 220-µm QW laser, with only a marginal increase in the intensity noise [25]. Recent results have also reported that the strong gain saturation in quantum dot (QD) lasers operating with GL effect can be beneficial for enhancing the 3-dB bandwidth at least by a factor of three as compared to the uniform bias condition [27], [28]. Such enhancements of the modulation efficiency with little effect on f R thus promises increased modulation bandwidths in GL DMLs.…”
Section: Introductionmentioning
confidence: 94%
“…A 22 dB modulation efficiency increase was also realized using a 220-µm QW laser, with only a marginal increase in the intensity noise [25]. Recent results have also reported that the strong gain saturation in quantum dot (QD) lasers operating with GL effect can be beneficial for enhancing the 3-dB bandwidth at least by a factor of three as compared to the uniform bias condition [27], [28]. Such enhancements of the modulation efficiency with little effect on f R thus promises increased modulation bandwidths in GL DMLs.…”
Section: Introductionmentioning
confidence: 94%
“…Uncharacteristically, it has never called explicitly on the photonics literature of small signal modulation of semiconductor lasers. Still a careful review of recent work [39] and legacy literature [40] shows that it was evident in multiple experimental and theoretical graphs [41].…”
Section: B Weak Couplingmentioning
confidence: 99%
“…Interestingly, it seems to have passed unnoticed in the photonics literature of small signal modulation of semiconductor lasers. A careful review of recent work [52] and [53], however, reveals that it was evident in a number of experimental and theoretical studies [54].…”
Section: Hopf Bifurcations and Modulation Responsementioning
confidence: 99%